Agréage des laits pour la transformation laitière : cas des yaourts de la laiterie littoral ( GIPLAIT ) MOSTAGANEM - YAKKACHE, Mohamed El Amine; DERRAR, Afif (My University, 2023)
The beneficial effects of fermented milks on human health are increasingly demonstrated. Physicochemical and microbiological analyzes were carried out on two fermented milk productions: "firm yoghurt and stirred yoghurt", these analyzes are based on a control going from the raw material to the finished product. The change in ph values is characterized by a drop to values of (4.41) and (4.43) for firm yoghurt and stirred yogurt respectively. In addition, there was an increase in dornic acidity up to (84.8 D0) for firm yoghurt and (85.64 D0) for stirred yogurt. Regarding the values of MG and East were variable between (0.75% - 26%) and (16.40% - 96%) respectively. The microbiological results showed a complete absence of pathogens as well as contamination, only the FTAM were noted (2.102UFC / 1g). All the results obtained show conformity of the two productions by contribution to the norms fixed by the company, which testifies on the good quality of the raw materials used, the mastery of the manufacturing process, the respect of the conditions of hygiene and safety.
Keywords: firm yogurt; stirred yoghurt; pH; Acidity; Est; MG